Higher Education in Portugal 1974-2009
XVIII, 430 p.
Keywords: A comprehensive, wide ranging and detailed account of the unfolding of higher education and higher education policy in Portugal from 1974 to 2009 by leading policy-makers and scholars, with the explicit purpose of showing how different disciplinary canons and perspectives contribute to the study of higher education and higher education policy including Law and Science Policy perspectives. Whilst focusing on one referential system, this book deals with current policy issues emerging in the wake of the post Bologna period. It also examines their long term historical origins in addition to the measures taken to address them. The substantive chapters are preceded by a detailed Introductory overview that places the issues treated in this volume in a solidly European perspective and sets out explicitly the differences in the dominant political, cultural and social values that set Portuguese as other Continental European systems of higher education apart from their Anglo Saxon counterparts.